2012
DOI: 10.1007/s00167-012-2167-3
|View full text |Cite
|
Sign up to set email alerts
|

Documentation of strength training for research purposes after ACL reconstruction

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 48 publications
0
14
0
1
Order By: Relevance
“…However, the level A1 systematic review of Augustsson71 concluded that the strength training programmes after ACLR should be further developed because it is still unclear what is the best way to train the quadriceps. To optimise outcome after rehabilitation, neuromuscular training should be added to strength training according to Gokeler et al 72 and Kruse et al 73.…”
Section: Resultsmentioning
confidence: 99%
“…However, the level A1 systematic review of Augustsson71 concluded that the strength training programmes after ACLR should be further developed because it is still unclear what is the best way to train the quadriceps. To optimise outcome after rehabilitation, neuromuscular training should be added to strength training according to Gokeler et al 72 and Kruse et al 73.…”
Section: Resultsmentioning
confidence: 99%
“…Augustsson 11 systematically reviewed 6 studies that documented strength training protocols after ACL reconstruction, and it was found that only 2 studies clearly documented the postoperative strength training protocol used in their study, suggesting a need for more accurate reporting of strength training protocols. Kristensen and Franklyn-Miller 101 reviewed the efficacy of resistance training for various musculoskeletal conditions, including ACL reconstruction.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the perceived value of exercise therapy following ACL injury and reconstruction, there is little certainty regarding its effectiveness and no clarity concerning specific therapeutic dosage and delivery. This stems from most trials after ACL injury not individualising interventions (ie, same programme for all patients) and failing to adequately document exercise frequency, intensity, volume and progression 51. Such a problem is not unique to the ACL field—it similarly affects implementation of rehabilitation for other musculoskeletal conditions 52.…”
Section: Discussionmentioning
confidence: 99%